How to Create Ideal Alar Form and Function - Davis, Richard E.; Ostby, Erin T. (Facial Plastic Surgery, 2020)
Refinement of the unsightly nasal tip lobule is one of the most common, yet also one of the most challenging aspects of cosmetic and functional rhinoplasty. In addition to meticulous analysis and precise surgical modification of the tip complex itself, successful tip refinement must also take into account the surrounding nose, especially the adjacent alar lobules. Unless the modified tip complex harmonizes with the adjacent alar lobules to form a symmetric, aesthetically pleasing, and fully functioning nasal base, tip refinement will inevitably fail. Structural interdependency between the alar lobules, the tip cartilages, and the nasal septum (and the myriad individual variations therein) make controlled alar complex refinement a formidable and complex undertaking. Long-term success is contingent upon understanding the full scope of structural tip dynamics, including not only the primary effects of tip refinement, but also potentially undesirable secondary effects that may deform the alae and thus compromise the surgical outcome.
Keywords: rhinoplasty; nasal ala; alar retraction; revision rhinoplasty